Enhancing English-Speaking Attitude through Role Play: A Lecturer-Teacher Collaborative Research Project - Utami, IGA Lokita Purnamika (Journal for Lesson and Learning Studies, 2023)
A collaborative research project between university lecturers and school teachers is a type of Continuing Professional Development (CPD) program that allows them to collaboratively analyze classroom problems and provide effective solutions. This study described the findings of a two-cycle collaborative Classroom Action Research project between a lecturer and a teacher in Indonesia. The study analyzes students' English-speaking attitudes. 8 meetings rich in role-play activities were designed to improve students' English-speaking attitudes by continuously analyzing and modifying instruction. The study was designed using the spiral cycle model. This model has four (four) steps: Plan - Actions - Observe - and Reflect. This study employed two data collection methods: interviews and observation. Data were analyzed in which includes data condensation, data display, and conclusions. This study reveals that there are four stages to implement Role play technique to increase students English-speaking attitudes. They are as follows: 1) The familiarization stage, which involves students connecting their prior knowledge with the topic 2) the rehearsal stage, which involves students rehearsing the role play; 3) the demonstration stage, which involves students demonstrating their role play; 4) the evaluation stage, which involves teacher and classmates providing feedback; and 5) the reflection stage, which involves students reflecting on their learning. Some teaching modifications that important in improving students' English-speaking attitudes and how the study develops teacher’s professionalism are discussed.